A Textual Analysis of Verbal Texts in the Children’s Picture Books - DEBBY YOLANDA; DIAN MARISHA PUTRI; TENGKU SILVANA (LINGUA: Jurnal Bahasa dan Sastra, 2017)
Abstract:The purpose of our study was to discover textual metafunction elements of the verbal text in one of the children‘s picture books entitled On the Move, part of the Wonderful World of English series. The data used in this research were lingual data of words, phrases taken from the particular picture book. The descriptive qualitative method was used in analyzing the data. The results of the study showed that the dominant element of the textual metafunction was topical themes and there were relations between textual elements and visual elements in making meaning from these children‘s picture books. Keywords: metafunction, theme, rheme, children’s picture books Abstrak: Tujuan dari penelitian kami adalah untuk menemukan elemen metafungsi tekstual dari teks verbal di salah satu serial buku anak-anak bergambar, Wonderful World of English bernama On the Move. Data yang digunakan dalam penelitian ini adalah kata dan frasa lingual yang diambil dari buku bergambar tersebut. Dalam menganalisis data digunakan metode deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa elemen dominan dari meta fungsi tekstual adalah tema topical dan adanya hubungan antara elemen tekstual dan elemen visual dalam pembuatan makna pada buku anak-anak bergambar ini. Kata-kata kunci: metafungsi, tema, rema, buku anak-anak bergambar